Exploring the Dimensions of Doctor-Patient Relationship in Clinical Practice in Hospital Settings - Saurabh RamBiharilal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Kerman University of Medical Sciences, 2014)
The Doctor-Patient Relationship (DPR) is a complex concept in the medical sociology in which patients voluntarily approach a doctor and thus become a part of a contract in which they tends to abide with the doctor's guidance. Globally, the DPR has changed drastically over the years owing to the commercialization and privatization of the health sector. Furthermore, the dynamics of the DPR has shown a significant change because of the formulation of consumer protection acts; clauses for professional misconduct and criminal negligence; establishment of patient forums and organizations; massive expansion of the mass media sector leading to increase in health awareness among people; and changes in the status of the doctors. Realizing the importance of DPR in the final outcome and quality of life of the patient, multiple measures have been suggested to make a correct diagnosis and enhance healing. To conclude, good DPR is the crucial determinant for a better clinical outcome and satisfaction with the patients, irrespective of the socio-cultural determinants.